Effects of Dietary Carbohydrate to Lipid Ratios on Growth Performance, Muscle Fatty Acid Composition, and Intermediary Metabolism in Juvenile Black Seabream (Acanthopagrus schlegelii) - Taj, Sehrish; Irm, Misbah; Jin, Min; Yuan, Ye; Andriamialinirina, Hardy Joël Timothée; Zhou, Qicun (Frontiers in Physiology, 2020)
An 8-week feeding trial was conducted to evaluate the effects of dietary carbohydrate to lipid (CHO:L) ratios on growth performance, muscle fatty acid composition, and intermediary metabolism in juvenile black seabream (Acanthopagrus schlegelii). Five isonitrogenous and isoenergetic diets (48.0% crude protein and 18.0 MJ kg–1 gross energy) were formulated to contain different CHO:L ratios ranging from 0.33 to 3.75. Triplicate groups of 20 fish averaging 0.51 ± 0.01 g were fed with experimental diets twice daily to apparent satiation. The results indicated that final body weight (FBW), percentage weight gain (PWG), specific growth rate (SGR), and protein efficiency ratio (PER) were significantly influenced by the dietary CHO:L ratios (p < 0.05). The highest FBW, PWG, and SGR were observed in fish fed the diet with a CHO:L ratio of 1.36 (p < 0.05). A two-slope broken-line regression analysis based on PWG indicated that the optimal dietary CHO:L is 1.08. Lipid content in the whole body decreased, and glycogen concentration in the liver increased with the increase of dietary CHO:L ratios from 0.33 to 3.75 (p < 0.05). Moreover, there was a positive correlation between muscle fatty acid composition and dietary fatty acid composition. The relative expression levels of genes involved in glucose metabolism, such as gk, pepck, and glut2 were upregulated by increasing the dietary CHO:L ratio. Also, the mRNA expression level of genes related to lipid synthesis, such as fas and accα were significantly upregulated with dietary CHO:L ratios increasing from 0.33 to 3.75. The highest expression of genes involved in fatty acid β-oxidation, such as cpt1 and acox1, were observed in fish fed the 1.36 CHO:L ratio diet. The gene expression of Δ6 fatty acyl desaturase (fads2) in the liver significantly increased with increase of dietary CHO:L ratios from 0.33 to 3.75. Fish fed the diet with CHO:L ratios of 2.26 and 3.75 had lower expression levels of elovl5 than those fed the other diets. These results demonstrate that dietary optimal CHO:L ratios could improve PWG and SGR but also influence expression of genes involved in glucose and lipid metabolism. Based on the overall results, the optimal dietary CHO:L ratio is 1.08 for black seabream.